The effect of physical exertion exercises using electrical muscle stimulation on the development of some physical and functional characteristics of women aged (40-45) years - Zuhad Fawzi; Dr. Mawahib Hameed (الرياضة المعاصرة)
The researchers have recently noticed the interest in the problem of overweight and how to find solutions to it until it is now at the forefront in terms of innovating various and different methods and treatment methods, and the interest in developing health fitness is one of the most important requirements of physical activity for the trainees, which led to the multiplicity of sports activities that promote the health aspect For the individual, in addition to the aesthetic aspect, the problem lies in not adopting training programs according to codified scientific foundations aiming, in addition to reducing weight, to raise the general health level of the trainee participating in fitness institutes, as the trainers do not follow the scientific method in codifying training curricula taking into account the individual differences between the trainees Which exposes them to sports injury problems, as the researchers decided to prepare a standardized training program by preparing physical exercises using EMS technology (electrical muscle stimulation) because it saves the time and effort required to lose weight and improve appearance in a fast and effective way, and to know its effect on some physical and functional characteristics of women aged (30) -45). And the aim of the research is to prepare and identify physical exertion exercises using electrical muscle stimulation in developing some physical and functional characteristics of women aged (40-45) years old, and the researchers used the experimental method of pre and post testing for the experimental and control groups, and the research community was identified as trainees in the student club hall Sports Activity / University of Baghdad, for the training season 2019-2020, whose number is (18) trainees, as the research sample was selected using the comprehensive inventory method and the sample was divided into two experimental groups and the control group with (9) trainees for each group. Physical effort was applied using electrical muscle stimulation on the experimental group for a period of time. Eight weeks, with three training units per week, and they used the SPSS statistical bag to process the data and obtain the results, from which the researchers came to the most important conclusions. Exercise physical exertion using electrical muscle stimulation has a positive effect on the development of some physical and functional characteristics of women aged (40-45) years